An Unusually Long Appendix: A Case Report and Literature Review - Todorovic, Slobodan; Toskovic, Borislav; Gačić, Jasna; Karaca, Hana; Colakovic, Natasa (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Acute appendicitis is one of the most common conditions in emergency surgery and appendectomy is the most frequently performed surgical procedure. The complexity of this pathology is reflected in the numerous congenital malformations and anatomical variations of the vermiform appendix. Anatomical variations are mainly related to its length and position. The average length of the appendix was found to be 9.5 cm in the male and 8.7 cm in the female, but different length has been reported, from 1 cm to even a 33 cm on the cadaver. CASE PRESENTATION: A 34-year-old man was admitted to the general surgery department due to symptoms that began the previous day. The patient complained of lumbar pain which later migrated to the periumbilical region and the right lower quadrant (RLQ) of the abdomen followed by fever, nausea, and vomiting. On clinical examination, he had a tenderness in RLQ with abdominal guarding. Laboratory analyzes showed leukocytosis and high markers of inflammation. Urinalysis and abdominal ultrasound were normal. Taking into consideration the clinical presentation and laboratory parameters, a decision was made to proceed for an open appendectomy. Intraoperatively, the appendix was inflamed, very long, partly retrocaecal, and partly paracolic in position, with two coils, extending upward. After dividing the mesoappendix, it measured 20 cm in length. The appendectomy was performed. Post-operative recovery was without complications. The patient was discharged from the hospital on the 3rd post-operative day. CONCLUSION: Although acute appendicitis is very frequent condition in emergency surgery, making the diagnosis could be challenging due to numerous differential diagnostic dilemmas. The position of the appendix and direction of its extension could lead to misdiagnosis. The synthesis of clinical examination, laboratory analyzes, and diagnostic procedures should lead clinicians to the right diagnosis and surgical treatment, avoiding possible complications and additional costs.